COMPORTAMENTO DE CARACTERES LIGADOS A PRODUÇÃO EM CANA DE AÇÚCAR - Bach, Sandro; Kruger, Cleusa a. M. B.; Silva, José A. G. d.; Dambrós, Diego; Silva, Adair J. d.; Battisti, Gabriel C.; Santos, Cleverson D. d.; Matter, Edegar; Brendler, João; Carollo, Alex (Salão do Conhecimento, 2013)
Resumo